2012
DOI: 10.1186/1471-2369-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycemia but not lipids is associated with abnormal urinary albumin excretion in diabetic kidney disease: a report from the Kidney Early Evaluation Program (KEEP)

Abstract: BackgroundThe relationship between glycemic control and lipid abnormalities with urinary albumin-creatinine ratio (ACR) in chronic kidney disease (CKD) patients with diabetes mellitus (DM) is unknown. We sought to investigate the association of dyslipidemia and glycemic control with levels of albuminuria in the National Kidney Foundation (NKF) Kidney Early Evaluation Program (KEEP) participants with DM and CKD stage 3 or higher.MethodsWe performed a cross-sectional study of 6639 eligible KEEP patients with DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In the Kidney Early Evaluation Program (KEEP) study of diabetic patients with CKD stage 3 to 5, only an elevated HDL-C level was associated with decreased odds of microalbuminuria [73]. There was no statistical significance between the albumin excretion rate and other lipid profiles in patients with T2D [73].…”
Section: Correlation Between Dyslipidemia and Diabetic Nephropathymentioning
confidence: 98%
See 1 more Smart Citation
“…In the Kidney Early Evaluation Program (KEEP) study of diabetic patients with CKD stage 3 to 5, only an elevated HDL-C level was associated with decreased odds of microalbuminuria [73]. There was no statistical significance between the albumin excretion rate and other lipid profiles in patients with T2D [73].…”
Section: Correlation Between Dyslipidemia and Diabetic Nephropathymentioning
confidence: 98%
“…However, only levels of triglycerides progressively increased with albuminuria, from normoalbuminuria to microalbuminuria and to macroalbuminuria [72]. In the Kidney Early Evaluation Program (KEEP) study of diabetic patients with CKD stage 3 to 5, only an elevated HDL-C level was associated with decreased odds of microalbuminuria [73]. There was no statistical significance between the albumin excretion rate and other lipid profiles in patients with T2D [73].…”
Section: Correlation Between Dyslipidemia and Diabetic Nephropathymentioning
confidence: 99%
“…Study by Bose et al [9] found association of microalbuminuria and macroalbuminuria with HbA1c levels, and no association was found for other measured lipids. Increase in HDL cholesterol was noted with decreased incidence of microalbuminuria, while no significant association of lipid markers was found with urinary ACR.…”
Section: Association Of Albumin To Creatinine Ratio With Cardiovasculmentioning
confidence: 90%
“…The mechanism of this may be linked to the increased levels of atherogenic lipoproteins promoted by endothelial dysfunction. [8,9] Albuminuria (>300mg/24 hours) or microalbuminuria (≥30 mg/24 hours to 300mg/24 hours), or albumin/creatinine ratio (≥30 mg/g), is used as a marker of renal damage and is used to define chronic kidney disease along with low estimated glomerular filtration rate (eGFR). [10] Both cardiovascular disease and diabetes mellitus share many risk factors in common (the "common soil" hypothesis), [11] also lipid metabolism has been extensively investigated in diabetes; little information is available whether urine ACR is associated with lipids and lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…In Kidney Early Evaluation Program (KEEP) participants with diabetes mellitus and CKD, increases in HDL levels were associated with decreased odds of moderately increased urine albumin excretion. However, overall glycemic control compared to dyslipidemia was a more significant predictor of increased albuminuria, a marker of CKD progression (Bose et al 2012). …”
Section: Dyslipidemiamentioning
confidence: 99%